Income distribution and exchange in a dynamic search model - Yilmaz, Ensar; Unveren, Burak (ELSEVIER, 2011)
This paper studies the link between income distribution and trade mechanisms in a dynamic search model with two-sided asymmetric information. Buyers and sellers have imperfect information about the income levels of the other group. Furthermore, asymmetry of information about incomes is the source of price dispersion. In such a frictional environment, we capture the effects of a change in inter- and intra-class income distribution on the trade mechanism, which is represented by the expected trade volume and the flux of buyers and sellers in the market. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Income distribution; Search; Asymmetric information; PRICE-COMPETITION; QUALITY; NETWORK; MARKET; Business & Economics